Analisis Kualitas Pelayanan Posyandu Wijaya Mustika 12 Di Kecamatan Mustikajaya Kota Bekasi - Aslamiyah, Su'ai Batul; Star, Yurisman (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Posyandu Wijaya Mustika 12 in Mustikajaya District, Bekasi City, is one of the government's efforts to improve maternal and child health. This study aims to analyze the quality of service, obstacles, and efforts to overcome obstacles at the Posyandu. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that the quality of service at Posyandu Wijaya Mustika 12 is good, but there are still some aspects that need to be improved. The main obstacles faced include frequent changes of cadres, the location of the posyandu which is not yet permanent, and the distance that is too far for service users. Efforts to overcome these obstacles include increasing cooperation, solidarity, and the quality of cadre work, increasing attention from the government and the community, and increasing accessibility and community enthusiasm.